Novel therapeutic approaches targeting matrix metalloproteinases in cardiovascular disease. - Briasoulis, A; Tousoulis, D; Papageorgiou, N; Kampoli, A; Androulakis, E; Antoniades, C; Tsiamis, E; Latsios, G; Stefanadis, C (2012)
Matrix metalloproteinases (MMPs), are proteinases that participate in extracellular matrix remodelling and degradation. Under normal physiological conditions, the activities of MMPs are regulated at the level of transcription, of activation of the pro-MMP precursor zymogens and of inhibition by endogenous inhibitors (tissue inhibitors of metalloproteinases; TIMPs). Alteration in the regulation of MMP activity is implicated in atherosclerotic plaque development, coronary artery disease and heart failure. The pathological effects of MMPs and TIMPs in cardiovascular diseases involve vascular remodelling, atherosclerotic plaque instability and left ventricular remodelling after myocardial infarction. Since excessive tissue remodelling and increased matrix metalloproteinase activity have been demonstrated during atherosclerotic lesion progression, MMPs represent a potential target for therapeutic intervention aimed at modification of vascular pathology by restoring the physiological balance between MMPs and TIMPs. This review discusses pharmacological approaches to MMP inhibition.